The Influence of Student's Understanding Level of ITE Law in Social Media - ., Hendriyadi; Malik, Anas; ., Muslim (KnE Social Sciences, 2024)
According to a Global WebIndex survey, social media is the longest-running platform, averaging 2.5 hours per day. Millennials are very proficient in using internet-based technology. The research objectives of writing a thesis made by the author were: 1) To find out the understanding of Sharia faculty students related to Law Number 11 of 2008. 2) To find out the understanding of Sharia faculty students related to Law No. 19 of 2016 concerning amendments to Law No. 11 of 2008 in social media. In this research, the author uses a quantitative approach method. This is a survey research, whose emphasis lies on relational research that studies the relationship of variables, so that direct or indirect hypotheses are always questioned. In this survey, information was collected using a questionnaire with a total of 150 respondents with descriptive statistical tests, classical assumption test, and hypothesis test. The hypothesis test results show the absence of influence on students’ understanding of the ITE Law by using social media. Keywords: ITE Law, social media, understanding